2015
DOI: 10.1016/j.msea.2015.01.066
|View full text |Cite
|
Sign up to set email alerts
|

Oxide dispersion strengthened nickel based alloys via spark plasma sintering

Abstract: Oxide dispersion strengthened (ODS) nickel based alloys were developed via mechanical milling and spark plasma sintering (SPS) of Ni-20Cr powder with additional dispersion of 1.2 wt.% Y 2 O 3 powder. Furthermore, 5 wt.% Al 2 O 3 was added to Ni-20Cr-1.2Y 2 O 3 to provide composite strengthening in the ODS alloy. The effects of milling times, sintering temperature, and sintering dwell time were investigated on both mechanical properties and microstructural evolution. A high number of annealing twins was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(17 citation statements)
references
References 49 publications
(47 reference statements)
2
14
0
Order By: Relevance
“…The average elastic modulus and hardness were measured as approximately 200 GPa and 5.5 GPa, respectively. As reported earlier, Ni-20Cr-1.2Y 2 O 3 -5Al 2 O 3 alloy has better mechanical properties than Ni-20Cr [19]. It can be noted from Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The average elastic modulus and hardness were measured as approximately 200 GPa and 5.5 GPa, respectively. As reported earlier, Ni-20Cr-1.2Y 2 O 3 -5Al 2 O 3 alloy has better mechanical properties than Ni-20Cr [19]. It can be noted from Fig.…”
Section: Resultssupporting
confidence: 74%
“…Gas atomized Ni-20Cr powder with nominal composition Ni-19.6Cr-0.2Fe-0.8Mn-0.9Si (wt.%) and mean particle size of 23.6±1.1 m, Y 2 O 3 powder with high purity (99.99%) and mean particle size of 30-40 nm, and Al 2 O 3 powder with 99.99% purity and mean particle size of 300-400 nm were all acquired from the American Elements Inc. The nominal compositions of Ni-20Cr, Ni-20Cr-1.2Y 2 O 3 and Ni-20Cr-1.2Y 2 O 3 -5Al 2 O 3 alloys were prepared via high energy ball milling using Spex 8000M shaker mixer/mill.Details of ball milling and SPS can be found in an earlier report [19]. The compressive creep experiments were performed at a temperature of 800 o C and a stress of 100 MPausing a 2320 model Applied Test Systemslever arm creep tester (Butler, PA, USA).For Transmission electron microscopy (TEM), a FEITecnai TF30-FEG STwin STEM operated at an accelerating voltage of 200kV was used.…”
Section: Methodsmentioning
confidence: 99%
“…Based on Equation (6), the ratio of σ ODS values for LMD-MA and HE-MA can be calculated by division, which indicates that the σ ODS of LMD-MA is nearly 4 times of that for HE-MA. Moreover, the compression strength of LMD-MA under different temperatures is compared with other alloys (Markus et al 2018;Zhang et al 2012;Pasebani et al 2015;Semiatin et al 2001;Shao et al 2019;Tao et al 2019;Zhang et al 2014;Kim et al 2018), as shown in Figure 14. Obviously, LMD-MA exhibits preferable high-temperature performance at elevated temperatures.…”
Section: The Relationship Between Microstructure and High-temperaturementioning
confidence: 99%
“…The addition of yttria increases strengthening, inhibits dislocation motion, increases the deformation resistance, controls the recovery and re-crystallization process and inhibits the grain growth [43]. As a result, the yttria-dispersed stainless steel sintered at 1000°C shows maximum yield stress than the yttria-free stainless steels.…”
Section: Compressive Strengthmentioning
confidence: 99%